School Quality Improvement through Transformational Leadership and Teacher Performance: A Study in Cengkareng District - Sri Rama Wijaya; Ihsana El Khuluqo; Istaryatiningtias Istaryatiningtias (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
The study aims to determine the influence of principal transformational leadership and teacher performance on the quality of public elementary schools in Cengkareng District. The research method employs a quantitative approach, utilizing survey techniques. One hundred nine public elementary school teachers from Cengkareng District, West Jakarta, participated in this study. The research instrument used a validated questionnaire covering three variables: the principal transformational leadership variable consists of the dimensions of ideal influence, inspirational motivation, intellectual stimulation, and individual consideration; the teacher performance variable consists of the dimensions of quantity, quality, speed and accuracy, time, and communication; and the school quality variable consists of the dimensions of content standards, process standards, graduate competency standards, educator and Education personnel standards, infrastructure standards, management standards, financing standards, and assessment standards—data analysis using regression test with the help of SPSS 24 Software. The study's results showed that 44.1% of the principal's transformational leadership influenced school quality, 27.2% of teacher performance influenced school quality, and 45.1% of the principal's transformational leadership and teacher performance simultaneously influenced school quality. The conclusion is that teacher effectiveness and the principal's transformative leadership affect the school's quality. Therefore, transformational leadership and teacher performance can be used to improve school quality.